Respostas
respondido por:
0
Resolvendo a potenciacao (2√3 + 3√2 / √6)², simplificando o resultado temos
(2√3 + 3√2 / √6)²
(2√3 + 3√2)²
---------------- =
(√6)²
FAZER POR PARTE ok!!!!!!!!!!!!!!!!!!!
(2√3)² = 2² (√3)² = 4 . 3 = 12
(3√2)² = 3² (√2)² = 9 . 2 = 18
(√6)² = 6
agora montar
(2√3 + 3√2)² 12 + 18 30
--------------- = -------------- = ------ = 5
(√6)² 6 6
(2√3 + 3√2 / √6)²
(2√3 + 3√2)²
---------------- =
(√6)²
FAZER POR PARTE ok!!!!!!!!!!!!!!!!!!!
(2√3)² = 2² (√3)² = 4 . 3 = 12
(3√2)² = 3² (√2)² = 9 . 2 = 18
(√6)² = 6
agora montar
(2√3 + 3√2)² 12 + 18 30
--------------- = -------------- = ------ = 5
(√6)² 6 6
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás